The Effect of CEO Gender, Director Reputation, and Institutional Ownership on the Quality of Financial Reporting in Manufacturing Firms Listed on the Indonesia Stock Exchange for the Period 2022–2024 - Salma Putri Sholihah; Shiwi Angelica Cindiyasari (Yayasan Riset dan Pengembangan Intelektual, 2025)
Examining the impact of CEO gender, director reputation, and institutional ownership on the quality of financial reports for manufacturing companies listed on the Indonesia Stock Exchange between 2022 and 2024 is the aim of this study. Based on data completeness criteria, 60 companies and 240 firm-year observations were selected by purposeful selection from the research population, which comprised 81 industrial organizations. The data was examined using multiple linear regression using SPSS 25. This was followed by classical assumption tests such as the autocorrelation, multicollinearity, heteroscedasticity, and normality tests. In contrast, director reputation demonstrates a significant negative influence, indicating that possessing a strong reputation does not necessarily lead to higher transparency in financial reporting. Meanwhile, institutional ownership shows a significant positive relationship with financial statement quality, emphasizing the vital monitoring function of institutional investors in corporate governance. With an adjusted R2 value of 32.8%, the three independent factors taken together have a considerable combined impact on the quality of financial statements. This suggests that factors beyond the scope of this model also have an impact on variations in reporting quality. Therefore, it may be said that the quality of financial statements is shaped by the interaction of ownership structure, board reputation, and leadership qualities. Consequently, enhancing financial reporting quality requires the support of additional corporate governance mechanisms that strengthen managerial transparency and accountability.